1998
DOI: 10.1097/00007632-199808150-00007
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Motion Study of the Whole Lumbar Spine by Videofluoroscopy

Abstract: Segmental instability influences the whole lumbar motion in patients with degenerative spondylolisthesis. The patients with chronic low back pain did not show a significant difference when compared with the volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 18 publications
3
71
0
Order By: Relevance
“…Takayanagi [12] studied the motion patterns in asymptomatic volunteers and symptomatic patients with L4-5 DS in sitting postures and found that lumbar spine with DS presented disordered motion patterns and segmental instability. Okawa [13] reported that patients with DS showed disordered motion patterns while subject bent forward from a standing neutral position and then returned to the original position. In this study, the kinematics of both anterior and posterior structures of the slipped vertebrae was evaluated and different gross motion patterns from normal vertebrae were observed, which agreed with the existing literatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takayanagi [12] studied the motion patterns in asymptomatic volunteers and symptomatic patients with L4-5 DS in sitting postures and found that lumbar spine with DS presented disordered motion patterns and segmental instability. Okawa [13] reported that patients with DS showed disordered motion patterns while subject bent forward from a standing neutral position and then returned to the original position. In this study, the kinematics of both anterior and posterior structures of the slipped vertebrae was evaluated and different gross motion patterns from normal vertebrae were observed, which agreed with the existing literatures.…”
Section: Discussionmentioning
confidence: 99%
“…Due to slippage, kinematics of the vertebrae with DS is altered, which may lead to a series of pathological processes and clinical symptoms. To reveal pathogenesis, explain clinical symptoms and decide treatment methods, kinematics of DS has been studied using a variety of techniques including lateral flexion-extension radiographs [10], biplanar radiographs [11], cineradiography [12,13], open MRI [14,15] and, etc. However, most of these studies focused on the anterior-posterior motion of the vertebral bodies.…”
Section: Introductionmentioning
confidence: 99%
“…The lumbar spine is a kinetic chain that requires the sharing of motion between levels during bending. Various aspects of intervertebral motion sharing have been investigated in cadaveric studies [17][18][19] in plain radiographic studies in vivo [20][21][22][23][24] and in continuous radiographic studies [3,5,8,20,[25][26][27][28][29][30]. Most of these have studied motion onset and displacement; however, two that studied displacement [4,24] and one that studied pattern variations [29], found differences between patients with CNSLBP and controls.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12] Despite considerable efforts over many years, no clear relationship has been established between low back pain and abnormal movement. [13][14][15][16][17][18] Most authors related abnormal translation to mechanical back pain. [11][12][17][18] A degree of translation motion is normally associated with flexion-extension due to the composite nature of spinal motion.…”
Section: Spinal Instabilitymentioning
confidence: 99%